2021
DOI: 10.3390/ijms22168773
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Autophagy and NLRP3 Inflammasome in Ischemia/Reperfusion Injury

Abstract: Ischemia/reperfusion (I/R) injury is characterized by a limited blood supply to organs, followed by the restoration of blood flow and reoxygenation. In addition to ischemia, blood flow recovery can also lead to very harmful injury, especially inflammatory injury. Autophagy refers to the transport of cellular materials to the lysosomes for degradation, leading to the conversion of cellular components and offering energy and macromolecular precursors. It can maintain the balance of synthesis, decomposition and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 99 publications
0
17
0
Order By: Relevance
“…NLRP3 inflammasome activation, lysosomal dysfunction and impaired autophagic flux play critical roles in the pathophysiology of I/R. In recent years, it has been found that macrophage autophagy plays a key role in NLRP3 activation during I/R [ 53 ]. In macrophages, lysosomes are at the center of key cellular processes that activate inflammasomes [ 54 , 55 ].…”
Section: Reviewmentioning
confidence: 99%
“…NLRP3 inflammasome activation, lysosomal dysfunction and impaired autophagic flux play critical roles in the pathophysiology of I/R. In recent years, it has been found that macrophage autophagy plays a key role in NLRP3 activation during I/R [ 53 ]. In macrophages, lysosomes are at the center of key cellular processes that activate inflammasomes [ 54 , 55 ].…”
Section: Reviewmentioning
confidence: 99%
“…In recent years, more and more evidence demonstrates that dysfunctional autophagy is related with many diseases, including ischemia/reperfusion injury. However, the related mechanisms are not fully clear [ 35 , 36 , 37 ].…”
Section: Overview Of Autophagymentioning
confidence: 99%
“…Reperfusion also provides abundant reoxygenation to ischemic tissue with rebbleeding (Suleyman and Ozcicek 2020). Therefore, ischemia/ reperfusion (I/R) is characterized by interruption of blood flow to organs followed by restoration of blood flow and reoxygenation (Lv et al 2021). Some mediators and cytokines that occur during the I/R process can cause a physiopathological process defined as secondary tissue injury.…”
Section: Introductionmentioning
confidence: 99%